Interfacial diffusion studies in Co-Pd layered films - Baker, A; Cerezo, A; PetfordLong, A (1996)
Position-sensitive atom probe microanalysis has been used to study diffusion in Co-Pd bilayers and multilayer films. Diffusion coefficients have been determined and the effect of grain boundaries on diffusion rates have been assessed.